Wederrechtelijk Study on the Treatment of Cadavers in the World of Medical Education - Sri Indarwati Mista'i Sjaf; Herowati Poesoko; Miftahul Munir (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The practice of anatomical corpse (cadaver) surgery in medical education has an important value to improve the understanding and skills of medical students related to the anatomy of the human body. However, uncivilized acts of the corpse in this practice can raise legal and ethical issues. This study aims to analyze whether the practice is in accordance with the principles of law, ethics, and respect for the corpse, as well as how the act of treating the corpse uncivilized can be categorized as an unlawful act (wederrechtelijk). The research uses a normative approach with primary, secondary, and tertiary legal analysis, including the Criminal Code, Law Number 17 of 2023 concerning Health, and Regulation of the Minister of Health Number 38 of 2022. The results of the study show that there is a gap in norms related to legal uncertainty in regulating the treatment of corpses in the practice of medical education. Existing norms have not explicitly provided detailed guidance on uncivilized acts, thus opening up space for multiple interpretations. The uncivilized treatment of corpses violates the principles of respect for human dignity as stipulated in criminal law and medical ethics. Therefore, systematic legal interpretation and regulatory reform are needed to provide legal certainty, protect the rights of the corpse, and ensure that the practice of medical education runs in accordance with the principles of ethics, law, and respect for the corpse. This study provides recommendations to strengthen regulations and ethical education in the use of cadavers in order to maintain public trust in the medical profession.